Composite coating modified negative electrode, all-solid-state battery and preparation method of all-solid-state battery

By using composite coating to modify the negative electrode in an all-solid-state battery, gel electrolyte, three-dimensional conductive material and two-dimensional sheet-shaped inorganic filler to form a "lithium-embedded chamber" and "insulating layer" structure, the problem of poor stability between the solid electrolyte and the metal lithium negative electrode is solved, and the cycle stability and service life of the battery are significantly improved.

CN119695155APending Publication Date: 2025-03-25SHENZHEN AUTOMOTIVE RES INST BEIJING INST OF TECH (SHENZHEN RES INST OF NAT ENG LAB FOR ELECTRIC VEHICLES) +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411791672.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In existing all-solid-state batteries, the poor stability between the solid electrolyte and the metal lithium negative electrode leads to lithium deposition and peeling, which increases the volume expansion and micro-short circuit problems of the battery during recycling.

Method used

The negative electrode is modified with a composite coating, including a composite coating composed of gel electrolyte, three-dimensional conductive material and two-dimensional sheet-like inorganic filler. The dual-function structure of "lithium embedded chamber" and "insulation layer" is formed through in-situ polymerization technology, improving the space and stability of lithium ion deposition.

Benefits of technology

It significantly improves the system expansion and micro-short circuit problems of all-solid-state batteries, and improves the service life and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695155A_ABST
    Figure CN119695155A_ABST
Patent Text Reader

Abstract

The invention discloses a composite coating modified negative electrode, an all-solid-state battery and a preparation method of the all-solid-state battery. The composite coating modified negative electrode comprises a metal layer and a composite coating, wherein the composite coating contains a gel electrolyte obtained through in-situ polymerization, a three-dimensional conductive material and a two-dimensional sheet-shaped inorganic filler; wherein the three-dimensional conductive material comprises one or more of three-dimensional porous carbon, a carbon nanotube and conductive carbon black; the two-dimensional flaky inorganic filler is selected from one or more of silver powder, indium powder, boron nitride, titanium nitride and graphene. The composite coating modified negative electrode can effectively improve the compatibility of a solid electrolyte and negative electrode metal, solves the problems of system expansion and micro short circuit of an all-solid-state battery, prolongs the service life of the all-solid-state battery, can be prepared through a near-dry method, does not need to use an organic solvent, and has the advantages of being green and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state batteries, and in particular to an all-solid-state battery containing a negative electrode modified by a composite coating. Background Art

[0002] An all-solid-state battery is a battery in which the positive electrode, negative electrode and electrolyte are all in solid form. Compared with batteries using liquid electrolytes, it has greater energy storage and output power and is safer.

[0003] The solid electrolytes used in all-solid-state batteries usually include four types: polymers, oxides, sulfides and halides. In order to achieve the goal of an all-solid-state battery with an energy density greater than 500Wh / kg, the positive electrode is usually a high-nickel, lithium-rich manganese-based active material, and the negative electrode is a metal lithium negative electrode or a lithium-free negative electrode. Among them, the stability between the solid electrolyte and the negative electrode, especially the metal lithium negative electrode, is one of the main factors affecting the performance of the all-solid-state battery. The oxide, sulfide and halide solid electrolytes used in the prior art will have side reactions with metal lithium, resulting in significant performance degradation of the corresponding all-solid-state batteries, and even inability to be recycled.

[0004] To solve the above problems, a commonly used technical means is to modify the surface of the metal lithium negative electrode by adding a coating, such as wet coating the metal lithium negative electrode with a mixture of a porous carbon material as an isolation layer, a metal silver powder as an ion transmission channel, and a binder PVDF to obtain a modified metal lithium negative electrode. However, in the modified negative electrode obtained by this method, the bonding stability between the coating material and the negative electrode material is poor, and it is impossible to overcome the lithium deposition and stripping phenomenon on the negative electrode side of the all-solid-state battery during charging and discharging. This phenomenon will further aggravate the volume expansion and micro-short circuit problems caused by the internal expansion of the battery cell during the cyclic use of the all-solid-state battery. Summary of the invention

[0005] In view of the defects of the prior art, the purpose of the present invention is to propose a new composite coating modified negative electrode and an all-solid-state battery and a preparation method thereof. The composite coating modified negative electrode can effectively improve the compatibility of the solid electrolyte with the negative electrode, especially metallic lithium, significantly improve the system expansion and micro-short circuit problems of the all-solid-state battery, and increase the service life of the all-solid-state battery.

[0006] The technical solution of the present invention is as follows:

[0007] A composite coating modified negative electrode, characterized in that it comprises: a metal layer formed by a metal that can be used as an all-solid-state battery negative electrode and a composite coating composited with the metal layer, wherein the composite coating comprises the following raw material components: a gel electrolyte obtained by in-situ polymerization, a three-dimensional conductive material and a two-dimensional flaky inorganic filler; wherein the three-dimensional conductive material is selected from one or more of three-dimensional porous carbon, carbon nanotubes, and conductive carbon black; the two-dimensional flaky inorganic filler is selected from one or more of silver powder, indium powder, boron nitride, titanium nitride, and graphene; in the composite coating, the mass content ratio of the gel electrolyte, the three-dimensional conductive material and the two-dimensional flaky inorganic filler is 50-80%: 1-20%: 0-50%.

[0008] In the above technical scheme of the present invention, the two-dimensional flaky inorganic filler has a high Young's modulus and can inhibit the growth of dendrites. The three-dimensional conductive material can construct an electron transmission channel inside the coating. After being combined with the two-dimensional flaky inorganic filler, a three-dimensional electron-ion transmission structure can be formed, and space for lithium ion deposition is provided to form a "lithium insertion chamber" for lithium ion embedding. The in-situ polymerized gel electrolyte can play a cross-linking role and has an ion transmission effect. The in-situ polymerized gel electrolyte can effectively isolate the electrolyte from the metal layer after being combined with the two-dimensional flaky inorganic filler and the three-dimensional conductive material to form an isolation layer. Therefore, the present invention constructs a structurally dense negative electrode coating with a dual-functional structure of "lithium insertion chamber" and "isolation layer" that can realize electron-ion conduction through the above technical scheme, which significantly reduces the volume expansion during the electrode cycle and improves the cycle stability of the all-solid-state battery.

[0009] According to some preferred embodiments of the present invention, the two-dimensional flaky inorganic filler includes a first inorganic filler and a second inorganic filler, wherein the first inorganic filler is silver powder and / or indium powder; and the second inorganic filler is selected from one or more of boron nitride, titanium nitride, and graphene.

[0010] More preferably, the inorganic filler includes silver powder and boron nitride.

[0011] The above preferred embodiments can form a composite structure of a first inorganic filler such as Ag-three-dimensional conductive material-a second inorganic filler such as boron nitride, wherein porous carbon constructs a three-dimensional ion-electron transmission channel inside the coating, and the second inorganic filler such as boron nitride has a hexagonal structure, which can provide a deposition space for lithium ions during the charge and discharge process. The cross-linked structure formed by the gel electrolyte through in-situ polymerization tightly connects the above composite structure as a whole, and cooperates with the silver powder to provide lithium ion transmission capability inside the coating.

[0012] According to some preferred embodiments of the present invention, the gel electrolyte includes the following raw material components in mass content: 10-20% of monomer, 1-5% of cross-linking agent, 40-70% of auxiliary agent, 10-30% of lithium salt and 0.1-1% of initiator, wherein the monomer is selected from one or more of butyl acrylate, methyl methacrylate, trifluoroethyl methacrylate and pentaerythritol triacrylate, the auxiliary agent is selected from one or more of EmimFSI, EmimTFSI, Py14FSI, PP14FSI, Py13TFSI, FEC, the lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate) and lithium tetrafluoroborate; the initiator is a photoinitiator and / or a thermal initiator.

[0013] According to some preferred embodiments of the present invention, the cross-linking agent is selected from one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polytetrafluoroethylene and a copolymer of polyvinylidene fluoride-hexafluoropropylene.

[0014] According to some preferred embodiments of the present invention, the initiator is selected from one or more of persulfate, 1-hydroxycyclohexyl phenyl ketone, diacyl peroxide and azobisisobutyronitrile.

[0015] According to some preferred embodiments of the present invention, the metal layer is a lithium metal layer and / or a stainless steel composite current collector layer, wherein the stainless steel composite current collector layer includes a stainless steel mesh layer with a porous mesh structure and a dense stainless steel foil layer, wherein the stainless steel mesh layer is in direct contact with the composite coating material.

[0016] In the above preferred embodiments of the present invention, when the metal layer is lithium metal, a metal lithium negative electrode can be obtained, and when the metal layer is a stainless steel composite current collector layer, a lithium-free negative electrode can be obtained.

[0017] According to some preferred embodiments of the present invention, the stainless steel mesh layer has a pore size of 1-20 μm and a thickness of 10-50 μm.

[0018] According to some preferred embodiments of the present invention, the thickness of the composite coating is 1-20 μm.

[0019] The present invention further provides a method for preparing the above composite coating modified negative electrode, which comprises:

[0020] (1) obtaining a raw material mixed solution of the gel electrolyte;

[0021] (2) adding the three-dimensional conductive material and the two-dimensional flaky inorganic filler to the raw material mixture of the gel electrolyte and uniformly dispersing them to obtain a coating slurry;

[0022] (3) extruding the coating slurry to obtain a coating sheet;

[0023] (4) rolling the coating sheet and the metal layer to obtain a composite sheet;

[0024] (5) hot pressing and curing the composite sheet to obtain the composite coating-modified negative electrode;

[0025] Wherein, step (2) comprises: adding all the required three-dimensional conductive materials and two-dimensional flaky inorganic fillers to the raw material mixed solution of the gel electrolyte, or dividing the gel electrolyte into several portions, adding a certain amount of three-dimensional conductive materials and / or two-dimensional flaky inorganic fillers to each portion of the gel electrolyte, and correspondingly obtaining a plurality of coating slurries, which are then extruded into a plurality of coating sheets through step (3), and then sequentially rolled and compounded with the metal layer to obtain the composite sheet.

[0026] The above preparation method of the present invention adopts a quasi-dry method, that is, using in-situ polymerization technology, by mixing the in-situ polymerized gel monomer with the inorganic material to form a dough-like composite precursor, and then rolling the composite precursor with metal lithium (or stainless steel foil) to obtain a coating-modified metal lithium (no negative electrode) precursor with a certain thickness, and finally obtaining a modified negative electrode by high-pressure thermal polymerization. The whole process does not require the participation of volatile solvents, nor does it require a solvent recovery device, and the mixing process is similar to dry mixing.

[0027] In a preferred embodiment, the three-dimensional conductive material is selected from porous carbon, the two-dimensional flaky inorganic filler is selected from silver powder, and steps (2) to (4) include:

[0028] (2) kneading and mixing the raw material mixture of silver powder, porous carbon and gel electrolyte at room temperature to obtain Ag-C coating slurry;

[0029] (3) extruding the Ag-C coating slurry into a sheet to obtain a coating sheet;

[0030] (4) The coating sheet and the metal lithium strip or the stainless steel composite current collector layer are rolled and composited by a double-roll press to obtain a composite sheet.

[0031] In another preferred embodiment, the three-dimensional conductive material is selected from porous carbon, the two-dimensional flaky inorganic filler is selected from silver powder and boron nitride, and steps (2) to (4) include:

[0032] (2) kneading the raw material mixture of boron nitride and a part of the gel electrolyte at room temperature to obtain NB coating slurry; kneading the raw material mixture of silver powder, porous carbon and the remaining gel electrolyte at room temperature to obtain Ag-C coating slurry;

[0033] (3) extruding the NB coating slurry and the Ag-C coating slurry into sheets respectively through an extruder to obtain a first coating sheet and a second coating sheet;

[0034] (4) The first coating sheet and the metal lithium strip or stainless steel composite current collector layer are roll-combined by a double-roll press to obtain a first composite sheet; the second coating sheet is placed on top of the first composite sheet and roll-combined by a roller press to obtain a second composite sheet.

[0035] According to some preferred embodiments of the present invention, the homogenization dispersion is achieved by a high shear internal mixer with a torque of 1-1000 N·m.

[0036] According to some preferred embodiments of the present invention, the extrusion temperature of the extrusion molding is 20-30°C.

[0037] According to some preferred embodiments of the present invention, the heat pressing curing is performed with a pressure of 1-20 MPa, a temperature of 40-80° C., and a time of 6-24 h.

[0038] The present invention further provides an all-solid-state battery containing the above composite coating-modified negative electrode.

[0039] The present invention has the following beneficial effects:

[0040] (1) The present invention improves the compatibility and stability between the negative electrode metal, especially lithium metal, and the solid electrolyte sulfide through coating modification;

[0041] (2) The composite coating obtained by the present invention has excellent electron-ion transport performance. During the battery charging and discharging process, lithium can be deposited between the coating and the current collector to prevent the deposited lithium from having a side reaction with the solid electrolyte sulfide;

[0042] (3) The composite coating obtained by the present invention has a specific two-dimensional-three-dimensional structure, and the modified negative electrode further formed can dynamically balance and complement the volume change generated by the battery during the cycle, reduce the volume expansion and micro-short circuit phenomenon of the battery system, and improve the cycle stability of the battery;

[0043] (4) The all-solid-state battery obtained by the present invention has excellent electrolyte-electrode compatibility and stability, has no obvious volume change in long-term cycle applications, and has excellent electrical performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a schematic diagram of the structure of the metal lithium negative electrode modified by the Ag-C-NB coating of Example 2.

[0045] Figure 2Schematic diagram of the structure of the lithium-free negative electrode modified by the Ag-C-NB coating of Example 4.

[0046] Figure 3 It is a comparison diagram of the first cycle capacity-voltage diagram of the all-solid-state battery obtained according to the negative electrode of Example 1-2 and Comparative Example 1 and the comparative battery;

[0047] Figure 4 The figure is a comparison chart of the cycle performance of the all-solid-state battery obtained according to the negative electrode of Examples 1-4 and the comparative battery;

[0048] Figure 5 This is a comparison chart of the cycle performance of all-solid-state batteries obtained using the negative electrodes of Examples 5-6. DETAILED DESCRIPTION

[0049] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.

[0050] The porous carbon used in the following examples and comparative examples is a three-dimensional porous carbon sphere; the pressure for hot pressing curing is controlled to be 10-30 MPa, and the curing time is 6-12 hours.

[0051] The cycle performance test method is: at a temperature of 25±2°C, perform (1): charge at 0.1C or a specified current to the termination voltage, and let it stand for 10 minutes; (2): discharge at 0.1C to the discharge final voltage, record the discharge capacity, and let it stand for 10 minutes; cycle (1)-(2) to test the battery cycle performance.

[0052] Example 1

[0053] The Ag-C coating-modified metallic lithium anode was prepared by the following steps:

[0054] (1) preparing an in-situ polymerized gel electrolyte solution, comprising: mixing a monomer MMA (methyl methacrylate), a crosslinking agent PEGDMA (polyethylene glycol dimethacrylate) and an auxiliary agent in a mass ratio of 1:1:1, adding an initiator AIBN (azobisisobutyronitrile) in an amount of 0.5 wt% of the monomer mass and a lithium salt LiTFSI in a concentration of 1 mol / L, stirring at room temperature until a solution state is obtained, and obtaining an in-situ polymerized gel electrolyte solution; wherein the auxiliary agent is a mixed solution obtained by mixing Py13FSI (1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide) and FEC (fluoroethylene carbonate) in a mass ratio of 1:1;

[0055] (2) preparing an Ag-C coating slurry, including: mixing silver powder, porous carbon and gel electrolyte solution at a mass ratio of 3:9:38 at room temperature to obtain an Ag-C coating slurry;

[0056] (3) extruding the Ag-C coating slurry into a sheet by an extruder to obtain a coating sheet, and rolling the coating sheet and the metal lithium strip through a double-roll press to composite, and adjusting the roller spacing to control the thickness of the coating sheet to 10 μm to obtain a composite sheet;

[0057] (4) The composite sheet is hot-pressed and cured in an oven at 60° C. to obtain a metal lithium negative electrode modified with an Ag-C coating.

[0058] Example 2

[0059] The Ag-C-NB coating-modified metallic lithium anode was prepared by the following steps:

[0060] (1) preparing an in-situ polymerized gel electrolyte solution, comprising: mixing a monomer MMA (methyl methacrylate), a crosslinking agent PEGDMA (polyethylene glycol dimethacrylate) and an auxiliary agent in a mass ratio of 1:1:1, adding an initiator AIBN (azobisisobutyronitrile) in an amount of 0.5 wt% of the monomer mass and a lithium salt LiTFSI in a concentration of 1 mol / L, stirring at room temperature until a solution state is obtained, and obtaining an in-situ polymerized gel electrolyte solution; wherein the auxiliary agent is a mixed solution obtained by mixing Py13FSI (1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide) and FEC (fluoroethylene carbonate) in a mass ratio of 1:1;

[0061] (2) preparing a coating slurry, including: mixing NB (boron nitride) and a gel electrolyte solution at a mass ratio of 1:1 at room temperature to obtain an NB coating slurry; mixing silver powder, porous carbon and a gel electrolyte solution at a mass ratio of 3:9:38 at room temperature to obtain an Ag-C coating slurry;

[0062] (3) Extruding the NB coating slurry into a sheet through an extruder to obtain a first coating sheet, and rolling the first coating sheet and the metal lithium strip through a double-roll press to composite, and adjusting the roller spacing to control the coating sheet thickness to 10 μm, to obtain a first composite sheet; and extruding the Ag-C coating slurry into a sheet through an extruder to obtain a second coating sheet, placing the second coating sheet on top of the first composite sheet through a roller press to composite, and adjusting the roller spacing to control the second coating sheet thickness to 10 μm, to obtain a second composite sheet;

[0063] (4) The second composite sheet is hot-pressed and cured in an oven at 60° C. to obtain a metal lithium negative electrode modified with a Ag-C-NB coating.

[0064] The structure of the Ag-C-NB coating-modified lithium metal anode is shown in the attached figure. Figure 1 As shown, it includes a metal lithium strip 13, an intermediate layer NB coating 12 located on the metal lithium strip 13, and a surface layer Ag-C coating 11 located on the NB coating 12; wherein the NB coating 12 has a three-dimensional ordered structure, which can provide space for lithium ion deposition and reduce volume expansion during the cycle process, and the Ag-C coating 11 has ion transmission and isolation functions.

[0065] Example 3

[0066] The Ag-C-NB coating-modified metal lithium negative electrode was prepared by the same process as in Example 2, except that the mass ratio of Ag powder to porous carbon was 2:1.

[0067] Example 4

[0068] The Ag-C-NB coating-modified metal lithium anode was prepared by the same process as in Example 2, except that the auxiliary agent was replaced by EmimFSI (1-ethyl-3-methyl-imidazolium bis(fluorosulfonyl)imidazolium).

[0069] Example 5

[0070] The same process as in Example 1 was adopted to prepare the Ag-C coating-modified lithium-free negative electrode, the only difference being that a porous composite stainless steel current collector was used instead of the metal lithium strip therein, wherein the porous composite stainless steel current collector had a two-layer structure, one layer of which was stainless steel with an ordered porous network structure and a thickness of 10 μm, and the other layer was a dense stainless steel foil.

[0071] Example 6

[0072] The same process as in Example 2 was adopted to prepare a lithium-free negative electrode modified with an Ag-C-NB coating, the only difference being that a porous composite stainless steel current collector was used instead of the metal lithium strip therein, wherein the porous composite stainless steel current collector had a two-layer structure, one layer of which was stainless steel with an ordered porous network structure and a thickness of 10 μm, and the other layer was a dense stainless steel foil.

[0073] The obtained Ag-C-NB coating modified lithium-free anode structure is as shown in the attached Figure 2 As shown, it includes a porous composite stainless steel current collector 24 containing a porous network structure layer 23, an intermediate layer NB coating 22 located on the porous composite stainless steel current collector 24, and a surface layer Ag-C coating 21 located on the NB coating 12; wherein, the NB coating 22 has a three-dimensional ordered structure, which can provide space for lithium ion deposition together with the porous composite stainless steel current collector 24 having a porous network structure layer 23, thereby reducing volume expansion during the cycle, and the Ag-C coating 21 has ion transmission and isolation effects.

[0074] Comparative Example 1

[0075] The Ag-C coating modified lithium metal negative electrode using PVDF as a binder is prepared by the following process: Ag powder, porous carbon and PVDF are mixed and dissolved in NMP solvent in a mass ratio of 1:3:1 to obtain a uniform coating slurry; the coating slurry is scraped on the surface of lithium metal with a scraper, and it is placed in a vacuum oven and dried at 80°C to obtain a Ag-C coating modified lithium metal negative electrode using PVDF as a binder.

[0076] The negative electrodes obtained in Examples 1-6 and Comparative Example 1 were assembled into an all-solid-state battery by the following process:

[0077] NCM811, LSPCl, and Superp were mixed in a mass ratio of 60:35:5 and ground in a mortar for 30 min to obtain a positive electrode material;

[0078] Weigh 150 mg of LSPCl and perform electrolyte film formation at 250 MPa to obtain a solid electrolyte membrane;

[0079] 35 mg of positive electrode material was weighed and placed on one side of the solid electrolyte membrane, and the positive electrode film was formed at 350 MPa. The negative electrode obtained in Example 1-4 was placed on the other side of the solid electrolyte membrane for full battery assembly. During the assembly, the pressure of the metal lithium negative electrode was controlled at about 60 MPa, and the pressure of the lithium-free negative electrode was controlled at about 250 MPa.

[0080] For comparison, the unmodified lithium metal negative electrode was assembled into an all-solid-state battery, i.e., a control battery, in the same manner for comparative testing.

[0081] The all-solid-state battery assembled above was subjected to a battery cycle performance test. Among them, the battery assembled according to the unmodified metal lithium negative electrode is battery 1#, the battery assembled according to the metal lithium negative electrode modified by the Ag-C coating of Example 1 is battery 2#, the battery assembled according to the metal lithium negative electrode modified by the Ag-C-NB coating of Example 2 is battery 3#, the battery assembled according to the lithium metal negative electrode modified by the Ag-C coating with PVDF as a binder in Comparative Example 1 is battery 4#, the battery assembled according to the metal lithium negative electrode modified by the Ag-C-NB coating of Example 3 is battery 5#, the battery assembled according to the metal lithium negative electrode modified by the Ag-C-NB coating of Example 4 is battery 6#, the battery assembled according to the lithium metal negative electrode modified by the Ag-C-NB coating of Example 4 is battery 7#, the battery assembled according to the lithium-free negative electrode modified by the Ag-C coating of Example 5 is battery 8#.

[0082] Among them, the first cycle capacity-voltage changes of 1# battery, 2# battery, 3# battery and 4# battery are shown in the attached figure. Figure 3As shown in the figure, the long cycle performance of 2# battery, 3# battery, 5# battery and 6# battery is shown in the attached figure. Figure 4 As shown in the attached figure, the long cycle performance of 7# battery and 8# battery is Figure 5 as shown.

[0083] From the attached Figure 3 It can be seen that the instability between pure metallic lithium and sulfide in the comparison battery leads to side reactions during battery charging, resulting in a sudden drop in voltage and inability to cycle; in the battery of comparative example 1, the coating only has electronic conductivity, and the first cycle of lithium is deposited on the surface of the coating, and is incompatible with the sulfide, resulting in a very low coulombic efficiency of the first cycle of the battery (30.34%), and a sudden voltage drop occurs in the second cycle, and the cycle cannot continue; in the sulfide all-solid-state battery with a lithium metal negative electrode modified with an electron-ion transport coating obtained according to Examples 1-2, the coating modification improves the compatibility and stability of metallic lithium and the sulfide electrolyte LSPCl, and improves the battery cycle stability.

[0084] From the attached Figure 4 It can be seen that different coating modification formulas have a certain influence on the performance of all-solid-state batteries. Among them, the capacity retention rate of the 3# battery with a metal lithium negative electrode modified by the Ag-C-NB coating is better than that of the 2# battery with a metal lithium negative electrode modified by the Ag-C coating, indicating that the ordered hexagonal boron nitride can further provide a place for lithium ion deposition, which helps to slow down the volume expansion of the all-solid-state battery during the cycle and improve the capacity retention rate of the battery in a long cycle; while keeping the coating components the same, changing the ratio of ion and electron transport components also has a certain influence on the performance of the battery. Among them, the performance of the 3# battery is better than that of the 5# battery, indicating that the matching between the ion transport component and the ionic conductivity of the coating can affect the battery performance of the all-solid-state battery.

[0085] On the other hand, the inventors unexpectedly discovered that the gel electrolyte also played an important role in the modified coating, among which different types of additives also had a certain influence on the battery cycle stability.

[0086] From the attached Figure 5 It can be seen that the capacity and retention rate of the 8# battery with lithium-free negative electrode modified with Ag-C-NB coating are better than those of the 7# battery with lithium-free negative electrode modified with Ag-C coating, indicating that the ordered hexagonal boron nitride can further provide a place for lithium ion deposition, which helps to slow down the volume expansion of the all-solid-state battery during the cycle and improve the capacity retention rate of the lithium-free negative electrode all-solid-state battery.

[0087] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A composite coating modified negative electrode, characterized in that: It comprises: a metal layer formed by a metal that can be used as a negative electrode of an all-solid-state battery and a composite coating compounded with the metal layer, wherein the composite coating comprises the following raw material components: a gel electrolyte obtained by in-situ polymerization, a three-dimensional conductive material and a two-dimensional flaky inorganic filler; wherein the three-dimensional conductive material is selected from one or more of three-dimensional porous carbon, carbon nanotubes, and conductive carbon black; the two-dimensional flaky inorganic filler is selected from one or more of silver powder, indium powder, boron nitride, titanium nitride, and graphene; in the composite coating, the mass content ratio of the gel electrolyte, the three-dimensional conductive material and the two-dimensional flaky inorganic filler is 50-80%: 1-20%: 0-50%.

2. The composite coating modified negative electrode according to claim 1, characterized in that: The two-dimensional flaky inorganic filler includes a first inorganic filler and a second inorganic filler, wherein the first inorganic filler is silver powder and / or indium powder; and the second inorganic filler is selected from one or more of boron nitride, titanium nitride, and graphene.

3. The composite coating modified negative electrode according to claim 1, characterized in that: The gel electrolyte comprises the following raw material components in mass content: 10-20% of monomer, 1-5% of cross-linking agent, 40-70% of auxiliary agent, 10-30% of lithium salt and 0.1-1% of initiator, wherein the monomer is selected from one or more of butyl acrylate, methyl methacrylate, trifluoroethyl methacrylate and pentaerythritol triacrylate, the auxiliary agent is selected from one or more of EmimFSI, EmimTFSI, Py14FSI, PP14FSI, Py13TFSI and FEC, the lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate) and lithium tetrafluoroborate; the initiator is a photoinitiator and / or a thermal initiator.

4. The composite coating modified negative electrode according to claim 4, characterized in that: in, The crosslinking agent is selected from one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polytetrafluoroethylene and polyvinylidene fluoride-hexafluoropropylene copolymer; and / or, the initiator is selected from one or more of persulfate, 1-hydroxycyclohexyl phenyl ketone, diacyl peroxide and azobisisobutyronitrile.

5. The composite coating modified negative electrode according to claim 1, characterized in that: The metal layer is a lithium metal layer and / or a stainless steel composite current collector layer, wherein the stainless steel composite current collector layer comprises a stainless steel mesh layer with a porous mesh structure and a dense stainless steel foil layer, wherein the stainless steel mesh layer is in direct contact with the composite coating material.

6. The composite coating modified negative electrode according to claim 5, characterized in that: The pore size of the stainless steel mesh layer is 1-20 μm, and the thickness is 10-50 μm.

7. The composite coating modified negative electrode according to any one of claims 1 to 6, characterized in that: The thickness of the composite coating is 1-20 μm.

8. The method for preparing a composite coating modified negative electrode according to any one of claims 1 to 7, characterized in that: It includes: (1) obtaining a raw material mixed solution of the gel electrolyte; (2) adding the three-dimensional conductive material and the two-dimensional flaky inorganic filler to the raw material mixture of the gel electrolyte and uniformly dispersing them to obtain a coating slurry; (3) extruding the coating slurry to obtain a coating sheet; (4) rolling the coating sheet and the metal layer to obtain a composite sheet; (5) hot pressing and curing the composite sheet to obtain the composite coating-modified negative electrode; Wherein, step (2) comprises: adding all the required three-dimensional conductive materials and two-dimensional flaky inorganic fillers to the raw material mixed solution of the gel electrolyte, or dividing the gel electrolyte into several portions, adding a certain amount of three-dimensional conductive materials and / or two-dimensional flaky inorganic fillers to each portion of the gel electrolyte, and correspondingly obtaining a plurality of coating slurries, which are then extruded into a plurality of coating sheets through step (3), and then sequentially rolled and compounded with the metal layer to obtain the composite sheet.

9. The preparation method according to claim 8, characterized in that: in, The homogenization dispersion is achieved by a high shear internal mixer with a torque of 1-1000 N·m; and / or, the extrusion temperature of the extrusion molding is 20-30°C; and / or, the pressure of the hot pressing curing is 1-20Mpa, the temperature is 40-80°C, and the time is 6-24h.

10. A composite coating modified negative electrode or An all-solid-state battery with a composite coating-modified negative electrode prepared by the preparation method according to claim 8 or 9.

Citation Information

Patent Citations

  • Composite electrolyte and application thereof

    CN111613830A

  • Interface protection film and a preparation method thereof, and application of interface protection film in lithium battery

    CN112210098A

  • Lithium-based electrode and secondary lithium battery

    CN113690407A

  • Solid-state composite metal lithium negative electrode with high electron / ion transmission characteristic as well as preparation method and application of solid-state composite metal lithium negative electrode

    CN114171716A

  • Protective layer of cathode interface of sulfide solid-state lithium-sulfur battery, preparation method and battery

    CN115692714A